Estimating the Genetic Diversity of Oranges Citrus spp. in South Sulawesi, Indonesia, Using RAPD Markers - Mustika Tuwo; Tutik Kuswinanti; Andi Nasruddin; Elis Tambaru (Scientifica)
Oranges hold significant economic importance, being cultivated extensively worldwide and having a large global market. Indonesia, ranked eighth globally as a producer of oranges, is one of the countries with high genetic diversity of oranges. This diversity is distributed across various regions of Indonesia, including South Sulawesi. Despite the advancements in DNA-based molecular marker techniques for assessing genetic diversity, information on orange diversity in South Sulawesi is currently unavailable and under-researched. In this study, random amplified polymorphic DNA (RAPD) markers were utilized to analyze the genetic diversity of oranges in five production centers in South Sulawesi. Leaf samples of 13 orange varieties were collected from the five production centers: Pangkep, Sidrap, Bantaeng, North Luwu, and Selayar in South Sulawesi, Indonesia. Genomic DNA extraction from the orange leaves followed the protocol of the DNA Mini Kit Geneaid. DNA amplification was carried out using the RAPD method with 14 primers: OPE-04, OPH-04, OPH-15, OPN-14, OPN-16, OPR-08, OPR-20, OPW-06, OPW-09, OPX-07, OPX-11, OPX-17, UBC-18, and UBC-51. The RAPD primers yielded 109 amplified fragments ranging in size from 200 to 2000 base pairs (bp), and all RAPD primers showed 100% polymorphism. The genetic diversity value (He) of oranges in South Sulawesi was moderate (0.236). Cluster analysis based on a similarity coefficient of 77% divided the 175 orange genotypes into five groups. The most closely related genotypes were SB6 and SB7, exhibiting 100% similarity, followed by genotypes JS8 and JS9 and JS13 and JS17, with genetic similarities exceeding 99% for each pair. Genotypes P9 and SI5 displayed the highest genetic distance, with a similarity coefficient of 57%. The dendrogram diagram can serve as a basis for selecting desired plant traits in the improvement of plant characteristics through both conventional breeding and genetic engineering activities.